MUSEUM TIMAH INDONESIA PANGKALPINANG SEBAGAI ALTERNATIF PEMBELAJARAN MATERI SUDUT - Fitri Apriani; Putri Cahyani Agustine (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
This aims of this study are to know the role of Museum Timah Indonesia Pangkalpinang context as alternative to understanding angles. This studi was using design research using Hypothetical Learning Trajectory (HLT) where research is conducted in three stages, namely initial design, teaching experiment (the pilot experiment) and retrospective analysis.this research was conducted at SD Negeri 29 Pangkalpinang. The data were collected through several things, namely by pre test and post test, video recording, collecting student work, interviews, and field notes. The results indicated that with the context of Museum Timah Indonesia Pangkalpinang, students could understand angle measurement. Students are more interested and motivated in completing angular measurements so that learning is more meaningful. PMRI can be used as an approach to learning angular measurements in elementary schools.